Pemanfaatan Biodegradable Film Pati Sagu sebagai Bahan Pengemas Permen Kelapa [Utilization of Biodegradable Film from Sago Starch as Packaging for Coconut-Based Candy] - Karouw, Steivie; Santosa, Budi; Kapu’allo, Maria L (Pusat Penelitian dan Pengembangan Perkebunan, 2020)
Packaging from natural biopolymers is the choice as a future packaging, because it is biodegradable so it does not have a negative effect on the environment. This study aims to determine changes in physicochemical, microbiological and sensory characteristics of coconut-based candy which are packaged using biodegradable film made from sago starch. The study was carried out from February to December 2016 at Laboratory of Indonesia Palm Crops Research Institute and Laboratory of Agricultural Technology Faculty, Gadjah Mada University. The research was conducted in two stages, namely preparation of biodegradable films in the first stage and the second stage of making coconut-based candy. The resulting coconut candy is then packaged using sago starch-based biodegradable film and then stored at room temperature for 40 days. Observations were made at 0, 10, 20, 30 and 40 days. The parameters observed were the composition of fatty acids, physicochemical properties (fat content, protein, water, ash and carbohydrates), microbiological tests (total microbes) and organoleptic tests. Coconut-based candy has a content of Medium Chain Fatty Acid (ALRM) of 62.15% and lauric acid is the highest proportion of fatty acids (52.05%). Coconut-based candy packaged using biodegradable films from sago starch for 40 days storage has a fat content (10.54-10.91%), protein (2.82-3.37%), water (4.05-4.71%) and ash (1.43-3.53%). Microbiological test showed that coconut candy packed using biodegradable films from sago starch in 30 days and 40 days storage was detected to contain a total of 6.67 CFU/g and 13.33 CFU/g respectively. Storage time that produces products that are still accepted by consumers is at 30 days of storage. The shelf life of coconut candy can be extended by addition of antioxidant and food preservatives.ABSTRAK Kemasan dari biopolimer alami menjadi pilihan sebagai pengemas masa depan, karena mudah terurai sehingga tidak memberikan efek negatif terhadap lingkungan. Penelitian ini bertujuan untuk mengetahui perubahan sifat fisikokimia, mikrobiologi dan sensoris permen kelapa yang dikemas menggunakan biodegradable film pati sagu. Penelitian dilakukan pada bulan Februari sampai Desember 2016 di Laboratorium Balai Penelitian Tanaman Palma Manado dan Laboratorium Fakultas Teknologi Pertanian, Universitas Gadjah Mada, Yogyakarta. Penelitian dilakukan dalam dua tahap, yaitu tahap pertama pembuatan biodegradable film dan tahap kedua pembuatan permen kelapa. Permen kelapa yang dihasilkan kemudian dikemas menggunakan biodegradable film pati sagu dan selanjutnya disimpan pada suhu ruang selama 40 hari. Pengamatan dilakukan pada 0, 10, 20, 30 dan 40 hari. Parameter yang diamati adalah komposisi asam lemak, sifat fisikokimia (kadar lemak, protein, abu air dan karbohidrat), uji mikrobiologi (total mikroba) dan uji organoleptik. Permen kelapa memiliki kandungan Asam Lemak Rantai Medium (ALRM) sebesar 62,15% dan asam laurat merupakan asam lemak dengan proporsi tertinggi (52,05%). Permen kelapa yang dikemas menggunakan biodegradable film pati sagu sampai penyimpanan 40 hari memiliki kadar lemak (10,54-10,91%), protein (2,82-3,37%), air (4,05-4,71%) dan abu (1,43-3,53%). Hasil uji mikrobiologi diperoleh bahwa permen kelapa yang dikemas menggunakan biodegradable film pati sagu pada penyimpanan 30 hari dan 40 hari terdeteksi mengandung total mikroba masing-masing sebanyak 6,67 CFU/g dan 13,33 CFU/g. Lama penyimpanan yang menghasilkan produk yang masih diterima konsumen yaitu pada 30 hari penyimpanan. Masa simpan produk dapat diperpanjang dengan penambahan antioksidan dan antimikroba